2021
DOI: 10.1186/s13012-021-01140-0
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to implementing evidence-based guidelines in long-term care: a qualitative evidence synthesis

Abstract: Background The long-term care setting poses unique challenges and opportunities for effective knowledge translation. The objectives of this review are to (1) synthesize barriers and facilitators to implementing evidence-based guidelines in long-term care, as defined as a home where residents require 24-h nursing care, and 50% of the population is over the age of 65 years; and (2) map barriers and facilitators to the Behaviour Change Wheel framework to inform theory-guided knowledge translation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 58 publications
5
74
0
4
Order By: Relevance
“…Tijdens een vergelijkbaar onderzoek in 2013 werd de richtlijn Opsporen oogafwijkingen (destijds Opsporing visuele stoornissen) net als in het huidige onderzoek het meest gebruikt zoals bedoeld [ 4 ]. Een andere overeenkomst met andere onderzoeken is dat de factor ‘onvoldoende tijd’ opvallend vaak als knelpunt wordt genoemd [ 4 , 10 , 11 ]. Dit gebrek aan tijd kan op twee manieren uitgelegd worden.…”
Section: Beschouwingunclassified
“…Tijdens een vergelijkbaar onderzoek in 2013 werd de richtlijn Opsporen oogafwijkingen (destijds Opsporing visuele stoornissen) net als in het huidige onderzoek het meest gebruikt zoals bedoeld [ 4 ]. Een andere overeenkomst met andere onderzoeken is dat de factor ‘onvoldoende tijd’ opvallend vaak als knelpunt wordt genoemd [ 4 , 10 , 11 ]. Dit gebrek aan tijd kan op twee manieren uitgelegd worden.…”
Section: Beschouwingunclassified
“…Prior to the meeting, the research team conducted a systematic review which identified barriers and facilitators to implementing evidence-based guidelines in LTC [31]. The barriers and facilitators identified from the systematic review were mapped on to COM-B components (e.g.…”
Section: Bcw Stage 1 -Understanding the Behaviourmentioning
confidence: 99%
“…Previous research reported that anxiety toward integrating innovations in practice is a common concern [ 12 ]. Implementing such changes into routine practice is recognized as challenging and its outcomes are unpredictable and uncertain [ 13 ]. As a consequence, researchers have investigated how to effectively implement change into clinical practice [ 14 ] by identifying factors that may impact implementation processes and using models, theories, and frameworks [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%